ANALISIS PENGARUH HARGA MINYAK DUNIA, KURS RUPIAH/US$, DAN FED RATE TERHADAP INDEKS SEKTORAL PASAR SAHAM DI INDONESIA (PERIODE JANUARI 2006 – DESEMBER 2016) - Pamungkas PAP, Bintang Surya; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2018)
Stock is one of investment instruments that have high risk. It happens because stock is very sensitive to macroeconomics change. There are many macroeconomic variables affecting stock prices including World Oil Price, Exchange Rate and Interest Rate. The previous study of macroeconomic effect on sectorial index has shows inconsistents results. The aim of this study is to investigate the effect of macroeconomic factors toward sectorial index at Indonesian Stock Market.Generalized AutoRegressive Conditional Heteroscedasticity (GARCH) method is used in this study to test proposed hypothesis. The period of January 2006 to December 2016 is used as a research sample by taking the monthly price of each variable, so that 132 samples are obtained. World oil price, exchange rate, and interest rate are used to explain macroeconomics variabels.The result of hypothesis testing by GARCH method shows that world oil pricesignificantly have positive effect to the index of agriculture sector, and mining sector. Then the rupiah exchange rate variables significantly have negative effect towards the nine existing sector indices. While the fed rate variable show positive effect to the index of infrastructure sector and trade sector.